Changes in Volatile Compound Composition of Kensington Pride Mango Pulp During Fruit Ripening - Herianus J.D Lalel (Jurnal Teknologi dan Industri Pangan, 2003)
Volatile compounds of ‘Kesington Pride’ mango produced from the pulp during fruit ripening were studied using headspace solid-phase microextraction (SPME) as a sampling method and gas chromatography with a flame ionisation detector (GC-FID) and gas chromatography mass spectrophotometry (GC-MS) for analysis. Ethylene production and respiration reached a peak on the second and third day of ripening, respectively. Seventy-eight volatile compounds were identified from the pulp of ‘Kesington Pride’ mango; however, only 73 volatile compounds were present in notable amount. The most abundant group of volatile compounds was monoterpenes, accounting for abaout 44% of the total identified compounds, followed by sesquiterpenes (19%), aldehydes (11%),esters (10%) aromatics (8%), alcohol (2%), ketones (2%), alkanes (1%) and norisoprenoid (1%). -Terpinolene was the major compound during ripening. Except for -pinene, 3,7-dimethl-1,3,7-octatriene, 4-methl-1 (1-methylethylidene)-cyclohexene, p-mentha-1,5,8-triene, aloocimene, the concentration of all other monoterpenes increased for the first six or eight days and decreased afterwards. All sesquiteroenes, p-cymene, p-cymen-9-ol,2-ethyl-1,4-dimethl benzene also increased during ripening and peaked on day four, six or eight of ripening. Ketones, aldehydes alkane and cis-3-hexenol, on the other hand, decreased during ripening. Ethanol, esters and norisoprenoid increased quite sharply at the end of ripening period. Key words : Manggo, aromatic, ripening.